EFEK ANTIINFLAMASI EKSTRAK ETANOLIK HERBA ALFALFA (Medicago sativa L.) PADA TIKUS JANTAN YANG DIINDUKSI KARAGENIN BESERTA IDENTIFIKASI KANDUNGAN SENYAWA AKTIFNYA - sri susilowati; yuniarti rosyidah (Universitas Wahid Hasyim Semarang, 2008)
ABSTRACTAlfalfa plant (Medicago sativa L.) contains of flavonoids compound, it has already known. One of the effects of flavonoids is anti-inflammatory effect of alfalfa herb (M. sativa L.). The purpose of this research to know about anti-inflammatory effect of alfalfa herb ethanolic extract on carragenan induced male rats and also to know the content of its active compound. Thirty male wistar rats were randomly divided into 5 group of 6. Group I, negative control, were treathed CMC-Na 0,5 %, group II, positive control, were treathed natrium diclofenac 6,3 mg/ kg BB. Group III, IV and V were treathed ethanolic extract of alfalfa herb orally dose 45 mg/ kg BW, 90 mg/ kg BW and 180 mg/ kg BW. Anti-inflammatory effect were measured of edema feet were done every 30 minutes for 6 hours using plestismometer. After edema feet data vs time got, then we can get AUC0-360 value and percentase anti-inflammatory effect. Statistic analytical used one way ANOVA (p<0,05) and continued with Tukey test then. Identification of active compound of alfalfa herb ethanolic extract was used Thiny Layer Chromatography (TLC). The result of the research shown that ethanolic extract of alfalfa herb by dosage 45 mg/ kg BW, 90 mg/ kg BW and 180 mg/ kg BW could reduce edema in carrageenan induced rats, significantly. The percentase of anti-inflammatory effect on dosage of 45 mg/ kg BW is 58,99 %, on 90 mg/ kg BW is 72,64 % and on 180 mg/ kg BW is 64,23 %. TLC result shown that active compound the ethanolic extract of alfalfa herbs was flavonoids. We could be concluded that ethanolic extract of alfalfa herb have anti-inflammatory effect. Key word : ethanolic extract of alfalfa herb (Medicago sativa L.), flavonoids, anti-inflammatory.